Insumos para una estrategia de egreso del Programa Juntos. Informe final - Zárate, Patricia; Barreto, Mariana; Durand, Anahí; Huber, Ludwig; Morel, Jorge (Instituto de Estudios Peruanos, PROYECTO CAPITAL, 2018)
Mayor información: http://repositorioproyectocapital.com/publicaciones/?buscar=Enbreve+31